Caracterización óptica de las lagunas Sauce Grande y Chasicó (provincia de Buenos Aires) - Bohn, V. Y. (2012)
The aim of this work was to evaluate the optical characteristics and the physical and chemicals parameters in order to determine zones in the Sauce Grande and Chasicó shallow lakes (Buenos Aires province). A portable spectroradiometer was used to obtain the reflectance spectra. The measurements were done in February, 2010. The chlorophyll-a values were obtained in laboratory from surface-derived water samples. A multiparameter probe was used to obtain the in situ parameters. Water transparency was estimated using a Secchi disc. As a result from the statistical analysis by the spectral signature from water, 3 zones were obtained in every lake. In Chasicó lake, the zone 1 represented the center-south area in the lake; the zone 2 was coincident with the NW in the lake whereas the zone 3 was related to the Chasicó river mouth. In Sauce Grande shallow lake, the subzones represented: the NNE area in the lake (zone 1); E and SE of the water body (zone 2) and the Sauce Grande river mouth (zone 3). The maximum depth in the Chasicó lake was 9 m whereas in Sauce Grande shallow lake was 1,50 m. As a consequence, the reflectance values in the Sauce Grande shallow pond surpassed the 8% and in the Chasicó lake the reflectance values did not surpass the 6%. Even though both water bodies are shallow, the effect from the bottom was more evident in the Sauce Grande lake than in Chasicó lake.